The role of tumor-associated macrophages in solid malignancies - an overview of current knowledge - Muri, Jozef; Chylikova, Jaroslava; Skarda, Jozef; Miklosova, Maria; Kamarad, Vojtech (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2022)
Tumor-associated macrophages are an important part of the tumor microenvironment. The presence of certain populations of macrophages within tumor tissue may be associated with either better or worse disease prognosis. The study of these cells is currently receiving a great deal of attention, with the most important topics of investigation raised being: the typification of subpopulations of tumor-associated macrophages; identification of the prognostic significance of population density and distribution of macrophages in the tumor microenvironment; ways to influence macrophage activity, migration and differentiation within the tumor. The answers to these questions can improve the efficiency of immunoterapy for malignancies. The presented article briefly reviews recent findings on tumor-associated macrophages in solid malignancies.
Keywords: Neoplasms; makrofágy; Macrophages; Tumor Microenvironment; alternatively activated macrophages (M2); nádorové mikroprostředí; prognóza; Humans; tumor-associated macrophages (TAMs); makrofágy spojené s nádory; classically activated macrophages (M1); nádory; Tumor-Associated Macrophages; resident tissue macrophages (NTAMs); tumor microenvironment (TME); Prognosis; lidé